Impact of physical activity on balance in people over 65 years of age - Rak, Justyna; Fajkiel, Kamila; Walkowiak, Klaudia; Błędowska, Sylwia; Badiuk, Nataliia (Journal of Education, Health and Sport, 2017)
The cause of aging society is the significant prolongation of life expectancy. With the aging process, there is progressive and permanent decrease in functional reserves and deterioration of homeostasis control. [1,2,3,4] By degenerative changes, there is imbalance and hence the frequency of falls, and therefore regular physical activity is important to restore, maintain, and maintain independence. [3,4,5,6] The study was performed by a patient aged 86, 56 kg and a height of 149 cm. Equilibrium assessment was performed using static posturography and the Four Squar Step Test (FSST) before and after a 10-day rehabilitation session under the supervision of a physiotherapist. The results of the exercise were improved in the test and posturography test with open eyes, while deterioration was indicated in the eyes with closed eyes.